Ideological Orientations in Pakistani Primary English Textbooks: A Critical Discourse Analysis - Zaheer, Asim; Waheed, Zubaria; Malik, Hadiqa (Pakistan Languages and Humanities Review, 2025)
This study inspects the various ideologies embedded within the Oxford University Press (OUP) English textbooks at the elementary level in Pakistan, questioning how pedagogical materials are used as a tool for expressing ideology. Its main aim is to investigate the spectrum of sociocultural, religious, and political discourses that are encoded in both the previous (2018) and the new (2021) Single National Curriculum (SNC) editions, and to identify the similarities and differences between them. Utilizing a qualitative research design, the study applies Fairclough’s three-dimensional model of Critical Discourse Analysis to explore the power relations, value CDA model, and ideologies behind the textual and visual stories. The study finds that both of the textbooks deliberately encode multiple dominant ideologies (religious, nationalistic, social and ethical) which aim to shape the moral consciousness and civic identity of the students. Although both editions reproduce the patriarchal structures that shape Pakistani society, the SNC aligned textbook makes a thin attempt to change the narrative by representing women in more participatory and public roles, but only within the conditioned approval of others. The study concludes by offering critical advice to textbook writers, curriculum writers and policy makers in the Punjab Department of Education to consider and understand the ideological implications of curriculum representation